Cultural and Heritage Protection in Customary Law: A Sustainability Perspective in the Global Era - Rangga Pratama Saputra (PT. Anagata Sembagi Education, 2025)
Globalization has had a significant impact on the sustainability of local culture and traditional heritage in Indonesia. The currents of cultural homogenization and the commodification of traditions often threaten values ​​​​preserved through customary law. This study aims to analyze the mechanisms for protecting culture and heritage through customary law within a sustainability framework, and to formulate a model for integrating customary law with formal law. The study uses a qualitative approach with literature study methods and normative-empirical analysis. Data were obtained from national and international regulations, scientific journal articles, and empirical case studies such as the practice of subak in Bali and sasi in Maluku. The results show that customary law contains effective internal mechanisms for preserving culture and the environment through collective regulation, rituals, and social sanctions. However, its effectiveness is often hampered by conflicting norms, limited legitimacy in the formal legal system, and globalization pressures that encourage cultural commodification. The discussion emphasizes the importance of an adaptive integration model, including hybridization of regional regulations, co-management mechanisms, dual legal forums, cultural impact assessments, and strengthening the capacity of customary institutions. In conclusion, customary law remains relevant as an instrument for protecting culture and heritage in the global era, but it requires formal legal support to function optimally. Adaptive integration between custom and the state is key to maintaining cultural sustainability while strengthening local identity.